The Scholarship System of the Universidad de Costa Rica: the regionalization and the student struggle - Robles Murillo, Keylor (2022)
This article analyzes the scholarship system of the University of Costa Rica (UCR), framed within the process of regionalization of public higher education, and the different collective actions carried out by students from the UCR campus on San Ramón, Alajuela. The latter aims to generate reflections on how poverty is conceived and measured, along with the process of centralization in decision-making within the University of Costa Rica. In addition, it follows up on one of the agreements voted at the 1st University Regionalization Congress, held in 1993 at the UCR. Regarding the methodology, a bibliographic inquiry was developed. Finally, the conclusions obtained from the channeled approach are mentioned.